Can livestock carrion availability influence diet of wintering red kites? Implications of sanitary policies in ecosystem services and conservation. Issue 4 (27th May 2014) - Blanco, Guillermo
Abstract: The diet of wintering red kites Milvus milvus over the last decade in central Spain was recorded to evaluate the influence of sanitary policies on carcasses use. The results show major differences in diet composition of red kites wintering in areas with and without availability of livestock carcasses. In the area without livestock carcasses (north‐western Madrid province), red kites fed on a similarly large proportion of wild lagomorphs across the study period. In the area with livestock farming (Segovia province), red kites exploited carcasses from different livestock schemes (stabled livestock—primarily swine—versus free‐ranging ruminants) depending on changing sanitary regulations as consequence of the Bovine Spongiform Encephalopathy or 'mad cow' crisis initiated in 2001. During the period of restrictive sanitary legislation (after the 'mad cow' crisis) that greatly limited the use of animal by‐products from ruminants as food for avian scavengers, kites mostly predated on common voles and scavenged on swine carcasses. After the implementation of the less restrictive regulations (since 2011; regulations CE1069/2009, CE142/2011) that again permitted the abandonment of extensive livestock remains in the countryside and in feeding stations, the proportion of ruminants in the kites' diet increased while the proportion of swine carrion decreased. Carcass dumps acted as temporally and spatially predictable sources of abundant food from stabled livestock before and even just after the mad‐cow crisis, but become relatively unpredictable foraging places afterwards due to the generalized carrion destruction in authorized plants, primarily of swine considered as non‐risk for the transmission of the bovine encephalopathy. This illustrates the deep and sometimes unexpected consequences that sanitary policies can impose on the composition and availability of food resources for scavenger wildlife. Much effort is still required to reconcile sanitary and environmental policies in order to ensure the conservation of avian scavengers and the provision of ecosystem services.